South American species of Paragordius Camerano, 1897 (Gordiida, Nematomorpha), with redescription of Paragordius minusculus and a description of a new species - Zanca, Fernanda Mariel (2006)
Paragordius is a genus of Gordiida with a worldwide distribution, but with a scarce specific diversity. Sixteen species of the genus Paragordius have been described so far. In many cases, as with the other genera of Gordiida, the original descriptions of the species are insufficient due to the limitations of the techniques employed. In this work the holotypes of P. minusculus and P. esavianus are redescribed by scanning electron microscopy (SEM), a new species of Paragordius is described, the distribution for P. esavianus and P. varius is enlarged and a new host record of P. esavianus is presented.